Effects of different wastewater characteristics and treatment techniques on the bacterial community structure in three pharmaceutical wastewater treatment systems - Ouyang, Erming; Liu, Yuan; Ouyang, Jiating; Wang, Xiaohui (Environmental technology, 2019)
Pharmaceutical wastewater is a typical type of wastewater with high concentrations of organic pollutants, but research on this subject is limited. The aeration tanks of three different pharmaceutical wastewater treatment systems were seeded with the same inocula and stably operated for 40 days. Then, aerobic sludge samples from the three aeration tanks were collected to provide insight into the bacterial community composition of the activated sludges. Additionally, we investigated the effects of wastewater characteristics and the type and operation of the technological system on the microbial communities. High-throughput sequencing analysis demonstrated that the communities enriched in the three reactors had differing. The dominant phyla detected were Proteobacteria, Chloroflexi, Bacteroidetes and candidate division TM7, while the dominant clones were uncultured Candidatus Saccharibacteria bacterium, uncultured Saprospiraceae bacterium, PHOS-HE51(AF314433.1), uncultured Anaerolineaceae bacterium and Blastocatella, suggesting their importance in pharmaceutical wastewater treatment plants. According to the wastewater parameters and canonical correspondence analyses, we can conclude that uncultured Candidatus Saccharibacteria bacterium, uncultured Anaerolineaceae bacterium and Blastocatella contribute to ammonium nitrogen ( ) removal; uncultured Saprospiraceae bacterium plays an important role in treating nitrogen; and chemical oxygen demand and PHOS-HE51 contribute to total phosphorus removal.